TOTAL QUALITY MANAGEMENT DALAM PENINGKATAN MUTU SERTIFIKASI PROFESI GURU - Irsan Habsyi (Jurnal Pendidikan dan Ekonomi (JUPEK), 2021)
Teachers are at the forefront of educating the nation's children through formal education, have social values for society, to become human beings with noble character in the field of science that is owned in accordance with the demands of today's education world. In Law Number 14 of 2005 article 8 concerning Teachers and Lecturers it is stated that teachers are required to have academic qualifications, competencies, educator certificates, physically and mentally healthy, and have the ability to realize national education goals. Each rule has a legal basis that binds every teacher to carry out his profession with the concept of education containing the values of national and state life based on Pancasila. Education must be a means to encourage the development of shared values and knowledge. But in the fact these values have not been used in formal education. This is seen as an inadequate approach to carrying out performance as a reliable professional educator. Teachers always emphasize the system of emphasis on students, it can be seen from the standard KKM scores which are still brought on average. Teachers who have certification have not shown their professionalism and are licensed as educated teachers. In the fact often occurs in schools is that teachers have not shown themselves in the teaching and learning process, because the factors that influence the emphasis on teachers are economic problems, lack of teacher discipline, inadequate infrastructure in schools, placement of teachers in the field of study. more than one person so that the teacher lacks teaching hours that should teach 24 hours a week.